A method for producing a copper-cerium master alloy

By processing copper-cerium master alloy melt using vacuum melting and electromagnetic stirring technology, the problems of rare earth element oxidation loss and compositional segregation were solved, achieving homogenization and high-quality production of copper-cerium master alloy.

CN117926046BActive Publication Date: 2026-11-06SHANGHAI JIAOTONG UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410064890.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-16
Publication Date
2026-11-06
Estimated Expiration
2044-01-16

AI Technical Summary

Technical Problem

In existing rare earth copper alloy preparation processes, rare earth elements are easily oxidized and burned off, and compositional segregation occurs due to differences in specific gravity, affecting the quality and stability of the intermediate alloy.

Method used

A vacuum melting furnace combined with electromagnetic stirring technology is used to control the stirring current, frequency and time, and non-contact stirring is carried out to ensure the homogenization of the copper-cerium master alloy melt.

Benefits of technology

This achieves uniformity in composition and microstructure of copper-cerium master alloys, improves product quality and stability, and avoids the introduction of additional impurity elements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117926046B_ABST
    Figure CN117926046B_ABST
Patent Text Reader

Abstract

This invention discloses a method for producing copper-cerium master alloy. The method employs a vacuum melting furnace combined with electromagnetic stirring technology, controlling the stirring current, frequency, and time to stir the alloy melt. After a period of settling, the melt is cast to obtain a copper-cerium master alloy ingot. This invention, based on the optimization of parameters such as stirring current, frequency, and time, controls the electromagnetic stirring process to ensure uniform mixing of the master alloy components, achieving homogenization of the composition and microstructure of the copper-cerium master alloy ingot. This improves the quality and stability of the master alloy product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of copper alloy materials technology, specifically a method for producing copper-cerium master alloy. Background Technology

[0002] Copper and copper alloys are considered fundamental materials supporting industrial economic development due to their excellent electrical and thermal conductivity and comprehensive mechanical properties. In recent years, while introducing advanced foreign technologies, my country has actively pursued independent innovation and has established a complete copper alloy industry system. However, there is still a significant gap between China and international advanced levels in some high-performance key copper alloy materials, with the development of rare earth copper alloy preparation processes being particularly slow.

[0003] Adding appropriate amounts of rare earth cerium can significantly improve the microstructure and properties of copper alloys: First, rare earth elements are chemically active and can adsorb a large number of impurity elements, purifying the alloy; second, rare earth elements can fill surface defects in the alloy phase, reduce surface tension at the interface, and improve casting performance; third, the refining and purifying effects of rare earth elements refine the alloy grains and reduce lattice distortion, thereby improving the mechanical and electrical properties of the alloy; fourth, rare earth elements can not only increase the electrode potential of the alloy, but also form a dense oxide layer on the alloy surface, improving the corrosion resistance of the alloy.

[0004] Currently, in industrial production, master alloy smelting is a mature and widely used method for producing rare earth copper alloys, often involving adding copper-rare earth master alloys to molten copper. However, rare earth elements are highly susceptible to oxidation and burn-off, causing the master alloy composition to deviate from the design. Furthermore, the significant difference in specific gravity between copper and rare earth elements leads to noticeable compositional segregation in the master alloy, which, due to the casting inheritance effect, affects the target alloy. Patents CN 105274383A and CN103911524A respectively disclose a method for preparing a multi-element rare earth copper master alloy through vacuum melting and a method for improving the preparation of copper-rare earth master alloys by adjusting the melting power to control the temperature and using mechanical stirring. These methods improve the quality of the master alloy from the perspectives of multiple composition designs and melting temperatures. However, the increase in alloy components and the use of mechanical stirring devices inevitably lead to excessive impurity elements, reducing the purity of the master alloy. Moreover, in mass production, it is difficult to achieve precise temperature control of the alloy melt across multiple batches, affecting the product quality stability of the master alloy. Summary of the Invention

[0005] To address the aforementioned problems, this invention provides a method for producing copper-cerium master alloys. The method employs a vacuum melting furnace combined with electromagnetic stirring technology, controlling the stirring current, frequency, and time to stir the alloy melt. After a period of settling, the melt is cast to obtain a copper-cerium binary master alloy ingot. This method allows for the non-contact electromagnetic stirring of the copper-cerium master alloy melt without introducing other components. By optimizing parameters such as stirring current, frequency, and time, the electromagnetic stirring process is controlled, achieving homogenization of the composition and microstructure of the copper-cerium master alloy ingot, improving the quality and stability of the product.

[0006] To achieve the above-mentioned objectives, the present invention adopts the following technical solution:

[0007] In a first aspect, the present invention provides a method for producing a copper-cerium master alloy, comprising the following steps:

[0008] S1. Pure cerium and pure copper are prepared as raw materials, and the casting module is preheated and kept at a constant temperature before being placed into the reactor;

[0009] S2. Place the raw materials prepared in step S1 into the reactor in the order of one layer of pure copper and one layer of pure cerium, and then evacuate the reactor.

[0010] S3. Slowly heat the reactor until the raw materials are completely melted to form a melt;

[0011] S4. Heat the melt and perform electromagnetic stirring;

[0012] S5. Reduce the melt temperature, allow it to stand and refine, then pour it into the casting module;

[0013] S6. After casting is completed, stop heating, maintain the gas pressure inside the reactor, and release the vacuum after the reactor cools down to a certain temperature to obtain a copper-cerium intermediate alloy.

[0014] As one embodiment of the present invention, in step S1, a certain mass ratio of pure copper and pure cerium is added according to the actual product requirements; the purity of the pure copper is 99.95 to 99.99 wt.%, and the purity of the pure cerium is 99.0 to 99.5 wt.%.

[0015] Furthermore, the mass ratio of pure copper to pure cerium is 19.5:80.5 to 20.5:79.5.

[0016] In one embodiment of the present invention, in steps S1, S2, S3, and S6, the reactor is a vacuum melting furnace.

[0017] In one embodiment of the present invention, in step S1, the casting module includes a cast iron wedge mold, a cast iron riser, and a casting funnel; the casting funnel is located 15-20 mm to the side of the melt outlet (i.e., the graphite crucible outlet). The furnace is a vacuum melting furnace.

[0018] In one embodiment of the present invention, in step S1, the preheating temperature is 350℃~400℃ and the heat preservation time is 2h~2.5h.

[0019] In one embodiment of the present invention, in step S2, industrial pure copper is cut into sheets according to the size of the graphite crucible in the vacuum melting furnace, and industrial pure cerium with a particle size of millimeters is prepared according to production requirements. The prepared raw materials are first loaded into the cleaned graphite crucible, and then the crucible is placed in the furnace.

[0020] In one embodiment of the present invention, in step S2, a vacuum is drawn until the internal pressure of the reactor is 10. -2 ~10 - 3 Pa.

[0021] In one embodiment of the present invention, in step S3, the heating temperature is 1100℃~1150℃. The melt temperature is measured by a temperature sensor, and the melting of the raw material in the graphite crucible is observed through a high-pressure vacuum observation hole.

[0022] In one embodiment of the present invention, in step S4, the temperature is raised to 1180℃~1200℃.

[0023] In one embodiment of the present invention, in step S4, the stirring current of the electromagnetic stirrer is 300±5A, the stirring frequency is 30±2Hz, and the stirring time is 20±1min. Electromagnetic stirring can ensure that the alloy melt is fully fused.

[0024] More preferably, the electromagnetic stirring current is 300A, the stirring frequency is 30Hz, and the stirring time is 20min.

[0025] In one embodiment of the present invention, in step S5, the temperature is reduced to 1140-1160°C, the standing refining time is 10-20 minutes, and the pouring speed is 0.2-0.3 kg / s; the crucible is tilted so that the (intermediate alloy) melt flows into the cast iron wedge mold along the casting funnel.

[0026] In one embodiment of the present invention, in step S6, the gas pressure inside the reactor is ≤10. -2 Pa, cooled to 350℃~400℃.

[0027] In this invention, the chemical composition of the copper-cerium master alloy ingot prepared in step S6 is determined, and the scanning microstructure morphology of the copper-cerium master alloy ingot is observed to determine the uniformity of the alloy microstructure composition.

[0028] Secondly, the present invention provides a copper-cerium master alloy prepared by the aforementioned method, wherein the copper-cerium master alloy comprises the following components by weight percentage: cerium 19.5-20.5 wt.%, with the balance being copper and trace impurities, the impurity content not exceeding 0.5 wt.%.

[0029] The beneficial effects of this invention are as follows:

[0030] 1. Due to the significant difference in specific gravity between rare earth elements and copper, obvious component segregation is easily generated, and rare earth elements readily react with impurities in the melt. This invention addresses these problems by incorporating non-contact electromagnetic stirring technology during vacuum melting. This avoids the burning loss of alloy components and, without introducing additional elements, results in a more uniform alloy composition and microstructure, thereby improving the quality and stability of the copper-cerium master alloy product.

[0031] 2. Under the melting temperature and vacuum conditions described in this invention, the alloy melt has good fluidity and is less prone to gas absorption during stirring. Based on this, by controlling the current, frequency and time of electromagnetic stirring, the advantages of electromagnetic stirring in alloy homogenization can be fully utilized, melt burn-off can be avoided as much as possible, thereby improving the alloy composition distribution and microstructure, and reducing element burn-off in rare earth alloy preparation.

[0032] 3. The copper-cerium master alloy product prepared by this invention is mainly used in the processing of high-performance rare earth copper alloys. It can ensure the composition of the target alloy, and the uniform structure of the master alloy under the influence of casting inheritance can improve the structure of the target alloy. Attached Figure Description

[0033] Other features, objects, and advantages of the present invention will become more apparent from the following detailed description of non-limiting embodiments with reference to the accompanying drawings:

[0034] Figure 1 The scanning microstructure of the copper-cerium alloy ingot in Example 1;

[0035] Figure 2 The scanning microstructure of the copper-cerium alloy ingot in Example 2;

[0036] Figure 3 The scanning microstructure of the copper-cerium alloy ingot in Example 3;

[0037] Figure 4 The scanning microstructure of the copper-cerium alloy ingot in Example 4;

[0038] Figure 5The scanning microstructure of the copper-cerium alloy ingot in Example 5;

[0039] Figure 6 The scanning microstructure of the copper-cerium alloy ingot in Example 6;

[0040] Figure 7 The scanning microstructure of the copper-cerium alloy ingot in Example 7;

[0041] Figure 8 The microstructure of a commercial copper-cerium alloy ingot for Comparative Example 1 is shown in the scanned image.

[0042] The dark-colored phase is the α-Cu phase, and the light-colored phase is the Cu-Ce phase. Detailed Implementation

[0043] The present invention will now be described in detail with reference to specific embodiments and the accompanying drawings. These embodiments will help those skilled in the art to further understand the present invention, but do not limit the invention in any way. It should be noted that those skilled in the art can make several changes and modifications without departing from the concept of the present invention. These all fall within the scope of protection of the present invention.

[0044] Example 1

[0045] The alloy composition adopts the CuCe20 grade, with Ce content of 20 wt.% and the balance being Cu and other unavoidable impurities;

[0046] According to the dimensions of the graphite crucible in the vacuum melting furnace, 99.95% pure industrial copper is cut into sheets. Industrial pure cerium with a particle size of millimeters and a purity of 99.0% is prepared according to production requirements. The prepared raw materials are loaded into the cleaned graphite crucible in a layer of pure copper followed by a layer of pure cerium, and then placed in the vacuum furnace. The cast iron wedge mold, cast iron riser, and casting funnel are preheated to 350°C and held for 2 hours. After preheating and assembly, they are placed in the furnace, with the casting funnel positioned 15mm to the side of the melt outlet. A vacuum is then created until the internal pressure of the furnace is 10... -2 Heating is initiated at Pa, and the heating power is controlled to slowly raise the furnace temperature to 1120℃. The melt temperature is measured using a temperature sensor, and the melting of the raw materials in the graphite crucible is observed through a high-pressure vacuum observation hole. After the raw materials in the crucible have completely melted, the melt temperature is raised to 1180℃, and an electromagnetic stirring device is used for appropriate stirring, controlling the stirring current at 300A, the stirring frequency at 30Hz, and the stirring time at 20min to ensure the alloy melt is fully integrated. After stirring, the melt temperature is appropriately reduced to 1140℃ and allowed to stand for refining for 15min. After standing, the crucible is tilted to allow the intermediate alloy melt to flow into the cast iron mold through the casting funnel at a pouring speed of 0.25kg / s. After the intermediate alloy is poured, heating is stopped, and the furnace pressure is maintained at ≤10. -2Pa was allowed to cool naturally in the furnace. When the temperature dropped to 350℃, the vacuum was gradually released, and the furnace door was opened to remove the copper-cerium master alloy ingot. The chemical composition of the copper-cerium master alloy ingot is shown in Table 1, and the scanning microstructure is shown in Table 2. Figure 1 .

[0047] Example 2

[0048] The difference from Example 1 is that the stirring current was controlled at 100A, the stirring frequency at 30Hz, and the stirring time at 20min, in order to compare the effect of different stirring currents on the alloy microstructure and composition; the chemical composition of the copper-cerium master alloy ingot is shown in Table 1, and the scanning microstructure is shown in Table 2. Figure 2 .

[0049] Example 3

[0050] The difference from Example 1 is that the stirring current was controlled at 500A, the stirring frequency at 30Hz, and the stirring time at 20min, in order to compare the effect of different stirring currents on the alloy microstructure and composition; the chemical composition of the copper-cerium master alloy ingot is shown in Table 1, and the scanning microstructure is shown in Table 2. Figure 3 .

[0051] Example 4

[0052] The difference from Example 1 is that the stirring current was controlled at 300A, the stirring frequency at 5Hz, and the stirring time at 20min, in order to compare the effect of different stirring frequencies on the alloy microstructure and composition; the chemical composition of the copper-cerium master alloy ingot is shown in Table 1, and the scanning microstructure is shown in Table 2. Figure 4 .

[0053] Example 5

[0054] The difference from Example 1 is that the stirring current was controlled at 300A, the stirring frequency at 55Hz, and the stirring time at 20min, in order to compare the effect of different stirring frequencies on the alloy microstructure and composition; the chemical composition of the copper-cerium master alloy ingot is shown in Table 1, and the scanning microstructure is shown in Table 2. Figure 5 .

[0055] Example 6

[0056] The difference from Example 1 is that the stirring current was controlled at 300A, the stirring frequency at 30Hz, and the stirring time at 5min, in order to compare the effect of different stirring times on the alloy microstructure and composition; the chemical composition of the copper-cerium master alloy ingot is shown in Table 1, and the scanning microstructure is shown in Table 2. Figure 6 .

[0057] Example 7

[0058] The difference from Example 1 is that the stirring current was controlled at 300A, the stirring frequency at 30Hz, and the stirring time at 45min, in order to compare the effect of different stirring times on the alloy microstructure and composition; the chemical composition of the copper-cerium master alloy ingot is shown in Table 1, and the scanning microstructure is shown in Table 2. Figure 7 .

[0059] The chemical composition of the results from the above embodiments was tested, and the results are shown in Table 1:

[0060] Table 1. Chemical composition (wt%) of copper-cerium master alloy ingots from Examples 1-7

[0061] element Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 Ce 19.993 19.914 19.825 20.091 19.780 20.033 19.875 Cu 79.929 80.018 80.108 79.835 80.154 79.901 80.052 Al 0.045 0.044 0.043 0.041 0.043 0.043 0.040 Zn 0.015 0.011 0.011 0.017 0.011 0.010 0.013 Si 0.018 0.013 0.013 0.016 0.012 0.013 0.020

[0062] Comparing the composition test results of Examples 1 to 7, it can be seen that the composition of intermediate alloy elements obtained by this method is within the permissible range of the target composition. Examples 3, 5 and 7 show that excessive stirring current, excessive stirring frequency and excessive stirring time can cause further burn-off of alloy component Ce to a certain extent.

[0063] from Figures 1-7 As can be seen, adjusting the stirring current, stirring frequency, and stirring time can improve the microstructure of the copper-cerium master alloy ingot. In Example 1, the alloy phases are the finest and most uniformly distributed, indicating that a stirring current of 300 A, a stirring frequency of 30 Hz, and a stirring time of 20 min are the most suitable process conditions for copper-cerium master alloys. A comparison of the microstructure of the copper-cerium master alloy produced using the method of this invention and a commercially available copper-cerium master alloy of the same composition is shown below. Figure 2 , Figure 8 As shown, the copper-cerium master alloy produced by the method of the present invention has a significantly finer and more uniform microstructure, indicating that the method of the present invention can significantly improve the microstructure of the copper-cerium master alloy.

[0064] The above results demonstrate that the method of the present invention, through vacuum melting combined with non-contact electromagnetic stirring technology, uniformly mixes rare earth elements and copper, two components with significantly different specific gravities, thereby significantly improving the microstructure of copper-cerium master alloy ingots. The copper-cerium master alloy prepared using this method has a fine and uniform microstructure, ensuring the composition of the target alloy, and further improving the microstructure of the target alloy through casting inheritance.

[0065] Specific embodiments of the present invention have been described above. It should be understood that the present invention is not limited to the specific embodiments described above, and those skilled in the art can make various changes or modifications within the scope of the claims, which do not affect the essence of the present invention. Unless otherwise specified, the embodiments and features described in this application can be arbitrarily combined with each other.

Claims

1. A method for producing a copper-cerium master alloy, characterized in that, Includes the following steps: S1. Pure cerium and pure copper are prepared as raw materials, and the casting module is preheated and kept at a constant temperature before being placed into the reactor; S2. Place the raw materials prepared in step S1 into the reactor in the order of one layer of pure copper and one layer of pure cerium, and then evacuate the reactor. S3. Heat the reactor until the raw materials are completely melted to form a melt; S4. Heat the melt and perform electromagnetic stirring; The electromagnetic stirrer has a stirring current of 300±5A, a stirring frequency of 30±2Hz, and a stirring time of 20±1min. S5. Reduce the melt temperature, allow it to stand and refine, then pour it into the casting module; S6. After casting is completed, stop heating, maintain the gas pressure inside the reactor, and release the vacuum after the reactor cools down to a certain temperature to obtain a copper-cerium intermediate alloy.

2. The production method according to claim 1, characterized in that, In step S1, the purity of the pure copper is 99.95~99.99 wt.%, and the purity of the pure cerium is 99.0~99.5 wt.%; the mass ratio of pure copper to pure cerium is 19.5:80.5~20.5:79.

5.

3. The production method according to claim 1, characterized in that, In step S2, a vacuum is drawn until the internal pressure of the reactor is 10. -2 ~10 -3 Pa.

4. The production method according to claim 1, characterized in that, In step S3, the heating temperature is 1100℃~1150℃.

5. The production method according to claim 1, characterized in that, In step S4, the temperature is raised to 1180℃~1200℃.

6. The production method according to claim 1, characterized in that, The electromagnetic stirrer has a stirring current of 300A, a stirring frequency of 30Hz, and a stirring time of 20min.

7. The production method according to claim 1, characterized in that, In step S5, the temperature is reduced to 1140~1160℃, the standing refining time is 10~20min, and the pouring speed is 0.2~0.3kg / s.

8. The production method according to claim 1, characterized in that, In step S6, the gas pressure inside the reactor is ≤10. -2 Pa, cooled to 350℃~400℃.

9. A copper-cerium master alloy prepared by any one of the production methods described in claims 1-8, characterized in that, The copper-cerium master alloy comprises the following components by weight percentage: cerium 19.5~20.5 wt.%, with the balance being copper and trace impurities, the impurity content not exceeding 0.5 wt.%.

Citation Information

Patent Citations

  • Preparation method of copper rare earth binary intermediate alloy

    CN103911524A

  • Rare earth (RE)-copper intermediate alloy and preparation method thereof

    CN105274383A

  • High-purify upper oxygen-free copper rod production method

    CN101491825A